2012
DOI: 10.1007/s10717-012-9391-7
|View full text |Cite
|
Sign up to set email alerts
|

Production of Ti3SiC2-based materials by SHS forced compaction of layered composite Ti–SiC

Abstract: A new method of synthesizing ceramic composite materials based on Ti 3 SiC 2 using non-powder reaction compositions of titanium and silicon carbide was developed. A ceramic composite with a Ti 3 SiC 2 -TiSi 2 matrix reinforced with SiC particles was obtained by SHS forced compaction of a multilayer packet of regularly packed layers of titanium foil and polymer film filled with silicon carbide particles. The particulars of the phase composition and microstructure of the material obtained were investigated.The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…A recent study, using titanium foils and polymer films highly filled with micro-sized SiC as starting materials [13], showed that the composition's result was quite close to our obtained material at a sintering temperature of 1400 ℃. The material was synthesized by SHS process and consisted of 72, 14, and 13 wt% of Ti 3 SiC 2 , SiC, and TiSi 2 , respectively, as well as traces of TiC and Ti 5 Si 3 C x .…”
Section: Wwwspringercom/journal/40145supporting
confidence: 85%
See 2 more Smart Citations
“…A recent study, using titanium foils and polymer films highly filled with micro-sized SiC as starting materials [13], showed that the composition's result was quite close to our obtained material at a sintering temperature of 1400 ℃. The material was synthesized by SHS process and consisted of 72, 14, and 13 wt% of Ti 3 SiC 2 , SiC, and TiSi 2 , respectively, as well as traces of TiC and Ti 5 Si 3 C x .…”
Section: Wwwspringercom/journal/40145supporting
confidence: 85%
“…However, regardless of the sintering temperature, the relative density increased with the increase of the holding time and became, for instance, higher than 99.9% for 20 min of holding time under a pressure of 60 MPa. According to the study of Istomin et al [13], the relative density of the material synthesized by SHS process, subjected to vacuum heat-treatment under a mechanical load 0.2 MPa, does not exceed 80%, whereas with the SPS technique, a high density close to the theoretical density, can often be achieved. The relationship between relative density of the material and the crystallite size of Ti 3 SiC 2 is represented by Fig.…”
Section: Wwwspringercom/journal/40145mentioning
confidence: 99%
See 1 more Smart Citation